Flame-retardant composite current collector and preparation method thereof

By using modified polypropylene resin and modified nanosilia-based flame retardant coatings in the composite fluid collection, the problems of insufficient bonding force and insufficient flame retardant performance in the composite fluid collection are solved, and higher flame retardant performance, mechanical properties and heat resistance are achieved.

CN119725552AActive Publication Date: 2025-03-28AI MU XI AI (SU QIAN) DIAN CHI JI SHU YOU XIAN GONG SI

Patent Information

Application Number
CN202411798849.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-28
Estimated Expiration
2044-12-09

AI Technical Summary

Technical Problem

The bonding force between the existing composite fluid-collection metal film layer and the base film layer is difficult to increase, resulting in an increase in failure risk. At the same time, its flame retardant performance is also insufficient, which cannot effectively prevent the risk of short circuit between the metal layers.

Method used

A base film layer consisting of modified polypropylene resin, reinforcement components, antioxidants, lubricants, coupling agents and compatibilizers are used, and a modified nanosilia-based flame retardant coating is applied to the surface of the metal film layer. Through the interaction and combination of these materials, the flame retardancy and mechanical properties of the composite material are improved.

Benefits of technology

The flame retardant properties, mechanical properties and heat resistance of the composite material are significantly improved, the interface compatibility and adhesion between the base film layer and the metal layer are enhanced, and the risks of failure and short circuit are effectively reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005177506800000251
    Figure BDA0005177506800000251
  • Figure BDA0005177506800000261
    Figure BDA0005177506800000261
Patent Text Reader

Abstract

The invention relates to the technical field of current collectors, in particular to a flame-retardant composite current collector and a preparation method thereof.The flame-retardant composite current collector is composed of a base film layer, metal film layers deposited on the two faces of the base film layer and flame-retardant layers formed by curing flame-retardant coatings and coated on the surfaces of the metal film layers; the preparation method comprises the following steps: S1, mixing the modified polypropylene resin, the reinforcing component, the antioxidant, the lubricant, the coupling agent and the compatilizer to obtain a mixture; s2, carrying out melt extrusion and tape casting on the mixture, and stretching through a two-way stretching process to form a base film layer; s3, metal film layers are deposited on the two faces of the base film layer, and hot press molding is conducted; s4, coating a flame-retardant coating, drying and curing to obtain the flame-retardant composite current collector, the prepared flame-retardant composite current collector has excellent flame retardance, excellent mechanical property and thermal aging resistance and high peel strength, the binding force of the metal film layer and the base film layer is firm, and the quality and safety of the composite current collector are effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of current collectors, and more specifically, to a flame retardant composite current collector and a preparation method thereof. Background Art

[0002] With the continuous development and large-scale application of the battery industry, people's requirements for battery quality and safety are getting higher and higher, which in turn requires battery companies to optimize and improve various components of the battery to improve the performance of the battery.

[0003] As one of the core components of the battery, the performance of the current collector directly affects the performance of the battery. In order to achieve the lightweight and safety of the current collector, the concept of the composite current collector came into being. The existing composite current collector adopts a "sandwich" structure, that is, a metal film layer + a base film layer + a metal film layer. This structure has attracted widespread attention from major battery manufacturers due to its advantages of high safety and high energy density, and has broad application prospects. However, the bonding force between the metal film layer and the base film layer of the composite current collector has always been a problem that is difficult to improve the production technology of the composite current collector, and it is also a common cause of failure of the composite current collector. In addition, flame retardant performance is a key safety indicator of the existing composite current collector. Due to the presence of the intermediate polymer base film layer, the existing composite current collector can effectively block the short circuit between the two metal layers, providing a certain degree of safety. However, whether it is holes in the polymer base film layer during the production process, or holes or melting due to high temperature during the use of the composite current collector, it will lead to the risk of short circuit between the metal layers, thereby seriously affecting the safety performance of the composite current collector. Summary of the invention

[0004] In order to solve the technical problems mentioned in the background technology, the present application provides a flame retardant composite current collector and a preparation method thereof.

[0005] In the first aspect, the present application provides a flame retardant composite current collector, which adopts the following technical solution:

[0006] A flame retardant composite current collector, comprising a base film layer, a metal film layer deposited on both sides of the base film layer, and a flame retardant layer formed by curing a flame retardant coating applied on the surface of the metal film layer;

[0007] Preferably, the base film layer is made of the following raw materials in parts by weight: 100-120 parts of modified polypropylene resin, 10-15 parts of reinforcing component, 0.5-2 parts of antioxidant, 1-3 parts of lubricant, 2-3 parts of coupling agent and 3-5 parts of compatibilizer.

[0008] Preferably, the flame retardant coating is made of the following raw materials in parts by weight: 10-12 parts of polymer matrix, 6-8 parts of modified nano-silicon dioxide, 1-2 parts of additives and 50-60 parts of solvent.

[0009] Preferably, the preparation of the modified polypropylene resin comprises the following steps:

[0010] (1) placing polypropylene and fluorinated ethylene propylene copolymer in a twin-screw extruder at a working temperature of 180-220° C. and mixing for 1.5-2 hours to obtain an intermediate 1;

[0011] (2) adding liquid crystal polymer to intermediate 1 at a working temperature of 230-250° C., mixing for 2-3 hours, extruding granulation, and cooling to obtain intermediate 2;

[0012] (3) Disperse the intermediate 2 in toluene, heat to 80-100°C, and stir while heating to obtain solution A. Add 4-trifluoromethylbenzoyl chloride toluene solution to solution A dropwise while stirring. Control the temperature at 60-80°C, add pyridine, react for 1-2h, filter, wash, and dry to obtain a modified polypropylene resin.

[0013] Preferably, in step (1), the mass ratio of polypropylene to fluorinated ethylene propylene copolymer is 15-20:3-6.

[0014] Preferably, the mass ratio of the intermediate 1 to the liquid crystal polymer in step (2) is 10-12:1-2.

[0015] Preferably, the mass ratio of the intermediate 2 to toluene in step (3) is 2-3:8-10.

[0016] Preferably, the mass concentration of the 4-trifluoromethylbenzoyl chloride toluene solution in step (3) is 12-15%.

[0017] Preferably, in step (3), the mass ratio of solution A, 4-trifluoromethylbenzoyl chloride toluene solution and pyridine is 80-100:15-20:0.1-1.

[0018] Preferably, the reinforcing component is composed of nano-montmorillonite and aramid fiber in a mass ratio of 5-8:1-2.

[0019] Preferably, the antioxidant is one or more of antioxidant 1010, antioxidant 168 and antioxidant 1425WL.

[0020] Preferably, the lubricant is one or more of zinc stearate, calcium stearate and polyethylene wax.

[0021] Preferably, the coupling agent is a silane coupling agent and / or a titanate coupling agent.

[0022] Preferably, the compatibilizer is maleic anhydride grafted polypropylene and / or ethylene-vinyl acetate copolymer.

[0023] Preferably, the metal film layer is one of a copper film, an aluminum film and a nickel film, and the thickness of the metal film layer is 1-5 μm.

[0024] Preferably, the deposition method is one of evaporation deposition, sputtering deposition, ion plating, electroplating and plasma enhanced chemical vapor deposition.

[0025] Preferably, the flame retardant coating is prepared by dispersing the polymer matrix, modified nano-silica and additives in a solvent, stirring and mixing, controlling the temperature to 200-230° C., the stirring speed to 300-400 rpm, and stirring for 1-2 hours to obtain the flame retardant coating.

[0026] Preferably, the polymer matrix is ​​polyurethane and / or polyacrylate.

[0027] Preferably, the auxiliary agent is a polycarboxylate dispersant and / or a silicone oil defoamer.

[0028] Preferably, the solvent is one or more of N-methylpyrrolidone, N,N-dimethylformamide and dimethyl sulfoxide.

[0029] Preferably, the preparation method of the modified nano-silicon dioxide comprises the following steps:

[0030] A1. After ultrasonic mixing of nano-silica, isopropanol, KH-570 and deionized water, the mixture was heated to 40-60°C, stirred for reaction for 4-5h, filtered, washed and dried to obtain epoxy nano-silica;

[0031] A2. Add epoxy nano-silica to the ethanol-phytic acid aqueous solution, disperse it by ultrasonic at 50-60°C for 30-50min, add the surface modification liquid dropwise, and after the addition is completed, heat it to 100-120°C and stir it for 2-3h, filter, wash and dry to obtain modified nano-silica.

[0032] Preferably, in step A1, the mass ratio of nano-silicon dioxide, isopropanol, KH-570 and deionized water is 10-12:30-40:3-4:45-55.

[0033] Preferably, the ethanol-phytic acid aqueous solution in step A2 is composed of phytic acid, anhydrous ethanol and deionized water in a mass ratio of 1-2:4-7:10-15.

[0034] Preferably, the surface modification liquid in step A2 is composed of tetraethylammonium bromide, 2-hydroxypyridine-3-carboxylic acid and anhydrous ethanol in a mass ratio of 0.1-0.2:2-3:15-20.

[0035] Preferably, in step A2, the mass ratio of the ethanol-phytic acid aqueous solution, epoxy nano-silica and the surface modification liquid is 10-12:3-4:0.5-1.

[0036] In a second aspect, the present application also provides a method for preparing a flame retardant composite current collector, comprising the following steps:

[0037] S1, adding modified polypropylene resin, reinforcing component, antioxidant, lubricant, coupling agent and compatibilizer into a high-speed mixer according to weight parts, and mixing uniformly to obtain a mixture;

[0038] S2, adding the mixed material into a twin-screw extruder for melt extrusion, casting and forming, and then stretching the formed material through a biaxial stretching process to form a base film layer;

[0039] S3, depositing metal film layers on both sides of the base film layer, and hot pressing forming;

[0040] S4. Apply 4-6 μm of flame retardant coating on the surface of the metal film layer, and after drying and curing, obtain a flame retardant composite current collector.

[0041] Preferably, in step S2, the tape casting speed is 1-2 m / min, and the tape casting temperature is 180-200°C.

[0042] Preferably, in the biaxial stretching process in step S2, the stretching temperature is 120-125° C., the stretching rate is 8-10 cm / s, the heat setting temperature is 210-230° C., and the stretching ratio is 4:1.

[0043] Preferably, the thickness of the base film layer in step S2 is 2-5 μm.

[0044] Preferably, in step S3, the hot pressing molding temperature is 120-180° C., the pressure is 1-2 MPa, and the time is 2-3 min.

[0045] Preferably, the curing temperature in step S4 is 120-150° C., and the curing time is 0.5-1 h.

[0046] In summary, this application has the following beneficial effects:

[0047] In the modification process of polypropylene resin, the present application first introduces fluorinated ethylene-propylene copolymer, and the fluorinated groups in the fluorinated ethylene-propylene copolymer improve the thermal stability and flame retardancy of the modified polypropylene resin, improve the barrier performance of the composite material to liquid electrolyte, and prevent the penetration of liquid electrolyte. Then, liquid crystal polymer and 4-trifluoromethylbenzoyl chloride are introduced to further modify the polyacrylate, which can significantly improve the compatibility of polypropylene resin with liquid crystal polymer and other components, make it more evenly dispersed in the composite material, enhance the mechanical properties of polypropylene resin, such as tensile strength, fracture toughness and modulus, and significantly improve heat resistance and chemical resistance. Nano-montmorillonite and aramid fiber are used as reinforcing components together. The lamellar structure of nano-montmorillonite and the anti-melting droplet performance of aramid fiber are combined, which can not only prevent the transfer of oxygen, combustible gas and heat, but also avoid the danger of secondary combustion and fire spread caused by molten droplets. In addition, nano-montmorillonite and aramid fiber can significantly improve the tensile strength, modulus and toughness of the base film layer, enhance the mechanical properties of the material, and effectively improve the interface compatibility between the base film layer and the metal layer, and improve the adhesion to the metal layer.

[0048] The present application adds modified nano-silica to the flame-retardant coating, which, on the one hand, exerts the flame retardancy and heat resistance of the nano-silica, and on the other hand, first introduces phytic acid into the reaction system, and the phosphate groups in the phytic acid molecules can undergo a ring-opening reaction with the epoxy groups on the surface of the epoxy nano-silica to form a stable ester bond, thereby increasing the functional group density on the surface of the nano-silica, forming a larger steric hindrance effect, and preventing agglomeration. In addition, the phytic acid molecules carry a negative charge and can be electrostatically bonded with tetraethylammonium bromide to form a positively charged protective layer, thereby enhancing the interfacial bonding force between the nano-silica and the polymer matrix. The hydroxyl and carboxyl groups in the 2-hydroxypyridine-3-carboxylic acid molecules can form a chelate bond with the active groups (such as epoxy groups and phosphate groups) on the surface of the nano-silica, thereby further enhancing the surface modification effect. The modified nano-silica is introduced into the polyurethane, and the carboxyl groups on the surface of the 2-hydroxypyridine-3-carboxylic acid are cross-linked with the amino groups on the polyurethane, thereby not only improving the compatibility of the nano-silica and the polyurethane, but also further improving the tensile strength, rigidity and fracture toughness of the composite material. DETAILED DESCRIPTION

[0049] The present application is further described in detail below with reference to the embodiments.

[0050] The polypropylene (brand name: M02-G) used in the examples and comparative examples of the present invention was purchased from Shanghai Yuanfeng Plastic Technology Co., Ltd.; the fluorinated ethylene propylene copolymer (brand name: L-2213) was purchased from Haozheng New Materials Technology (Dongguan) Co., Ltd.; the liquid crystal polymer (brand name: E5008L BK) was purchased from Dongguan Hongwang Plastic Co., Ltd.; 4-trifluoromethylbenzoyl chloride was purchased from Hubei Xinghengye Technology Co., Ltd.; nano-montmorillonite (model: DK-NF) was purchased from Zhejiang Huate New Materials Co., Ltd.; aramid fiber (model: WAL34) was purchased from Dongguan Yichen Plastic Raw Materials Co., Ltd.; maleic anhydride grafted polypropylene (article number: HH7250BTBMY4) was purchased from Dongguan Zhangmutou Hengtai Plastic Raw Materials Business Department; polyurethane (brand number: A85P4441) was purchased from Dongguan Kaiwan Engineering Plastic Raw Materials Co., Ltd.; dimethyl silicone oil was purchased from Jinan Silicon Port Chemical Co., Ltd.; nano-silica (article number: BTH-5018) was purchased from Lingshou County Ruojia Mineral Products Co., Ltd.; KH-570 was purchased from Dongguan Hongrui Chemical Co., Ltd.; tetraethylammonium bromide was purchased from Shanghai Hongzhuang Chemical Technology Co., Ltd.; 2-hydroxypyridine-3-carboxylic acid was purchased from Hubei Watson Chemical Technology Co., Ltd., and phytic acid (article number: 01-92-5) was purchased from Shaanxi Rankang Biotechnology Co., Ltd.

[0051] Embodiment 1-3 provides a flame retardant composite current collector and a preparation method thereof.

[0052] Example 1

[0053] A flame-retardant composite current collector is composed of a base film layer, a metal film layer deposited on both sides of the base film layer, and a flame-retardant layer formed by curing a flame-retardant coating coated on the surface of the metal film layer; the base film layer is made of the following raw materials in parts by weight: 100 parts of modified polypropylene resin, 10 parts of reinforcing components, 0.5 parts of antioxidants, 1 part of lubricants, 2 parts of coupling agents, and 3 parts of compatibilizers; the flame-retardant coating is made of the following raw materials in parts by weight: 10 parts of polymer matrix, 6 parts of modified nano silicon dioxide, 1 part of auxiliary agent, and 50 parts of solvent; wherein the reinforcing component is composed of nano montmorillonite and aramid fiber in a mass ratio of 5:1, the antioxidant is antioxidant 1010, the lubricant is zinc stearate, the coupling agent is γ-aminopropyl triethoxysilane, the compatibilizer is maleic anhydride grafted polypropylene, the polymer matrix is ​​polyurethane, the auxiliary agent is dimethyl silicone oil, and the solvent is N-methylpyrrolidone.

[0054] Wherein, the preparation of modified polypropylene resin comprises the following steps:

[0055] (1) placing polypropylene and fluorinated ethylene propylene copolymer in a mass ratio of 5:1 in a twin-screw extruder at a working temperature of 180° C. and mixing for 1.5 h to obtain an intermediate 1;

[0056] (2) adding liquid crystal polymer to intermediate 1, controlling the mass ratio of intermediate 1 to liquid crystal polymer to be 10:1, operating temperature to be 230° C., mixing for 2 h, extruding granulation, and cooling to obtain intermediate 2;

[0057] (3) Disperse the intermediate 2 in toluene, heat to 80°C, stir while heating, the stirring speed is 300 rpm, and the stirring time is 10 min to obtain solution A; wherein the mass ratio of the intermediate 2 to toluene is 1:4, and dropwise add a 4-trifluoromethylbenzoyl chloride toluene solution with a mass concentration of 12% to solution A, and control the dropping time to 15 min. Meanwhile, continue stirring, control the temperature to 60°C, add pyridine, and control the mass ratio of solution A, 4-trifluoromethylbenzoyl chloride toluene solution and pyridine to 80:15:0.1, react for 1 h, filter, wash, and dry at 60°C to constant weight to obtain a modified polypropylene resin.

[0058] The preparation method of modified nano-silicon dioxide comprises the following steps:

[0059] A1. After mixing nano-silica, isopropanol, KH-570 and deionized water, ultrasonic power 50W, ultrasonic frequency 40kHz, ultrasonic for 30 minutes at room temperature, heating to 40°C, stirring for 4 hours, stirring speed 400rpm, filtering, washing and drying to obtain epoxy nano-silica, wherein the mass ratio of nano-silica, isopropanol, KH-570 and deionized water is 10:30:3:45;

[0060] A2. Add epoxy nano-silica to the ethanol-phytic acid aqueous solution, ultrasonically disperse it at 50°C for 30 minutes, with an ultrasonic power of 100 W and an ultrasonic frequency of 45 kHz, and dropwise add the surface modification liquid for 10 minutes. After the addition is completed, heat it to 100°C, stir it for 2 hours, filter, wash and dry it to obtain modified nano-silica, wherein the ethanol-phytic acid aqueous solution is composed of phytic acid, anhydrous ethanol and deionized water in a mass ratio of 1:4:10, the surface modification liquid is composed of tetraethylammonium bromide, 2-hydroxypyridine-3-carboxylic acid and anhydrous ethanol in a mass ratio of 0.1:2:15, and the mass ratio of the ethanol-phytic acid aqueous solution, epoxy nano-silica and the surface modification liquid is 10:3:0.5.

[0061] A method for preparing a flame retardant composite current collector comprises the following steps:

[0062] S1, adding modified polypropylene resin, reinforcing component, antioxidant, lubricant, coupling agent and compatibilizer into a high-speed mixer according to weight parts, and mixing at a speed of 600 rpm at room temperature for 45 minutes to obtain a mixture;

[0063] S2, adding the mixed material into a twin-screw extruder, heating to 220°C, heating for 1 hour, melt extruding, and casting at a speed of 1m / min and a temperature of 180°C, and then stretching the formed material through a biaxial stretching process to form a base film layer with a thickness of 2μm, wherein the stretching temperature is 120°C, the stretching rate is 8cm / s, the heat setting temperature is 210°C, and the stretching ratio is 4:1;

[0064] S3, sputtering and depositing a copper film layer with a thickness of 1 μm on both sides of the base film layer, with a sputtering power of 480 W, a sputtering voltage of 180 V, a sputtering temperature of 150° C., a hot pressing molding temperature of 120° C., a pressure of 1 MPa, and a time of 2 min;

[0065] S4, coating a 4 μm flame retardant coating on the surface of the copper film layer using a slot extrusion coater, drying at 50° C. for 2 h, and curing at 120° C. for 0.5 h to obtain a flame retardant composite current collector;

[0066] The preparation method of the flame retardant coating is as follows: disperse the polymer matrix, modified nano-silica and additives in a solvent, stir and mix, control the temperature to 200° C., stir at 300 rpm, stir for 1 hour, and obtain the flame retardant coating.

[0067] Example 2

[0068] A flame-retardant composite current collector is composed of a base film layer, a metal film layer deposited on both sides of the base film layer, and a flame-retardant layer formed by curing a flame-retardant coating coated on the surface of the metal film layer; the base film layer is made of the following raw materials in parts by weight: 110 parts of modified polypropylene resin, 12 parts of reinforcing components, 1 part of antioxidant, 2 parts of lubricant, 2.5 parts of coupling agent, 18 parts of filler and 4 parts of compatibilizer; the flame-retardant coating is made of the following raw materials in parts by weight: 11 parts of polymer matrix, 7 parts of modified nano silicon dioxide, 1.5 parts of auxiliary agent and 55 parts of solvent; wherein the reinforcing component is composed of nano montmorillonite and aramid fiber in a mass ratio of 6:1.5, the antioxidant is antioxidant 1010, the lubricant is zinc stearate, the coupling agent is γ-aminopropyl triethoxysilane, the compatibilizer is maleic anhydride grafted polypropylene, the polymer matrix is ​​polyurethane, the auxiliary agent is dimethyl silicone oil, and the solvent is N-methylpyrrolidone.

[0069] Wherein, the preparation of modified polypropylene resin comprises the following steps:

[0070] (1) placing polypropylene and fluorinated ethylene propylene copolymer in a mass ratio of 18:5 in a twin-screw extruder at a working temperature of 200° C. and mixing for 1.8 h to obtain an intermediate 1;

[0071] (2) adding liquid crystal polymer to intermediate 1, controlling the mass ratio of intermediate 1 to liquid crystal polymer to be 11:2, operating temperature to be 240° C., mixing for 2.5 h, extruding granulation, and cooling to obtain intermediate 2;

[0072] (3) Disperse intermediate 2 in toluene, heat to 90°C, stir while heating, the stirring speed is 350 rpm, and the stirring time is 15 min to obtain solution A; wherein the mass ratio of intermediate 2 to toluene is 2.5:9, and add 4-trifluoromethylbenzoyl chloride toluene solution with a mass concentration of 14% to solution A for 20 min while continuously stirring, and control the temperature to 70°C, add pyridine, and control the mass ratio of solution A, 4-trifluoromethylbenzoyl chloride toluene solution and pyridine to 90:18:0.5, react for 1.5 h, filter, wash, and dry at 70°C to constant weight to obtain modified polypropylene resin.

[0073] The preparation method of modified nano-silicon dioxide comprises the following steps:

[0074] A1. After mixing nano-silicon dioxide, isopropanol, KH-570 and deionized water, ultrasonic power was 75W, ultrasonic frequency was 45kHz, and ultrasonic was carried out at room temperature for 35 minutes. Then, the temperature was raised to 50°C, stirred for reaction for 4.5 hours, and the stirring speed was 500rpm. After filtering, washing and drying, epoxy nano-silicon dioxide was obtained, wherein the mass ratio of nano-silicon dioxide, isopropanol, KH-570 and deionized water was 11:35:3.5:50;

[0075] A2. Add epoxy nano-silica to the ethanol-phytic acid aqueous solution, ultrasonically disperse it at 55°C for 40 minutes, with an ultrasonic power of 110 W and an ultrasonic frequency of 48 kHz, and dropwise add the surface modification liquid for 13 minutes. After the addition is completed, heat it to 110°C, stir it for 2.5 hours, filter, wash and dry it to obtain modified nano-silica, wherein the ethanol-phytic acid aqueous solution is composed of phytic acid, anhydrous ethanol and deionized water in a mass ratio of 1.5:5:12, the surface modification liquid is composed of tetraethylammonium bromide, 2-hydroxypyridine-3-carboxylic acid and anhydrous ethanol in a mass ratio of 0.15:2.5:18, and the mass ratio of the ethanol-phytic acid aqueous solution, epoxy nano-silica and the surface modification liquid is 11:3.5:0.8.

[0076] A method for preparing a flame retardant composite current collector comprises the following steps:

[0077] S1, adding modified polypropylene resin, reinforcing component, antioxidant, lubricant, coupling agent and compatibilizer into a high-speed mixer according to weight parts, mixing at a speed of 700 rpm at room temperature for 50 min, and mixing evenly to obtain a mixture;

[0078] S2, adding the mixed material into a twin-screw extruder, heating to 250°C, heating for 1.5 hours, melt extruding, casting at a speed of 1.5 m / min and a temperature of 190°C, and then stretching the formed material through a biaxial stretching process to form a base film layer with a thickness of 3 μm, wherein the stretching temperature is 123°C, the stretching rate is 9 cm / s, the heat setting temperature is 220°C, and the stretching ratio is 4:1;

[0079] S3, sputtering and depositing a copper film layer with a thickness of 3 μm on both sides of the base film layer, with a sputtering power of 500 W, a sputtering voltage of 190 V, a sputtering temperature of 160° C., a hot pressing molding temperature of 150° C., a pressure of 1.5 MPa, and a time of 2.5 min;

[0080] S4, coating a 5 μm flame retardant coating on the surface of the copper film layer using a slot extrusion coater, drying at 55° C. for 2.5 h, and curing at 135° C. for 0.8 h to obtain a flame retardant composite current collector;

[0081] The preparation method of the flame retardant coating is as follows: disperse the polymer matrix, modified nano-silica and additives in a solvent, stir and mix, control the temperature to 220° C., the stirring speed to 350 rpm, stir for 1.5 hours, and obtain the flame retardant coating.

[0082] Example 3

[0083] A flame-retardant composite current collector is composed of a base film layer, a metal film layer deposited on both sides of the base film layer, and a flame-retardant layer formed by curing a flame-retardant coating coated on the surface of the metal film layer; the base film layer is made of the following raw materials in parts by weight: 120 parts of modified polypropylene resin, 15 parts of reinforcing components, 2 parts of antioxidants, 3 parts of lubricants, 3 parts of coupling agents, and 5 parts of compatibilizers; the flame-retardant coating is made of the following raw materials in parts by weight: 12 parts of polymer matrix, 8 parts of modified nano silicon dioxide, 2 parts of auxiliary agents, and 60 parts of solvents; wherein the reinforcing component is composed of nano montmorillonite and aramid fiber in a mass ratio of 4:1, the antioxidant is antioxidant 1010, the lubricant is zinc stearate, the coupling agent is γ-aminopropyl triethoxysilane, the compatibilizer is maleic anhydride grafted polypropylene, the polymer matrix is ​​polyurethane, the auxiliary agent is dimethyl silicone oil, and the solvent is N-methylpyrrolidone.

[0084] Wherein, the preparation of modified polypropylene resin comprises the following steps:

[0085] (1) placing polypropylene and fluorinated ethylene propylene copolymer in a mass ratio of 10:3 in a twin-screw extruder at a working temperature of 220° C. and mixing for 2 h to obtain an intermediate 1;

[0086] (2) adding liquid crystal polymer to intermediate 1, controlling the mass ratio of intermediate 1 to liquid crystal polymer to be 6:1, operating temperature to be 250° C., mixing for 3 h, extruding granulation, and cooling to obtain intermediate 2;

[0087] (3) Disperse the intermediate 2 in toluene, heat to 100°C, stir while heating, the stirring speed is 400 rpm, and the stirring time is 20 min to obtain solution A; wherein the mass ratio of the intermediate 2 to toluene is 3:10, and dropwise add a 15% mass concentration of 4-trifluoromethylbenzoyl chloride toluene solution to solution A, control the dropping time to 30 min, and continue stirring at the same time, control the temperature to 80°C, add pyridine, control the mass ratio of solution A, 4-trifluoromethylbenzoyl chloride toluene solution and pyridine to 100:20:1, react for 2 h, filter, wash, and dry at 80°C to constant weight to obtain a modified polypropylene resin.

[0088] The preparation method of modified nano-silicon dioxide comprises the following steps:

[0089] A1. After mixing nano-silica, isopropanol, KH-570 and deionized water, ultrasonic power 100W, ultrasonic frequency 50kHz, ultrasonic for 40 minutes at room temperature, heating to 60°C, stirring for 5 hours, stirring speed 600rpm, filtering, washing and drying to obtain epoxy nano-silica, wherein the mass ratio of nano-silica, isopropanol, KH-570 and deionized water is 12:40:4:55;

[0090] A2. Add epoxy nano-silica to the ethanol-phytic acid aqueous solution, ultrasonically disperse it at 60°C for 50 minutes, with an ultrasonic power of 120 W and an ultrasonic frequency of 50 kHz, and dropwise add the surface modification liquid for 15 minutes. After the addition is completed, heat it to 120°C, stir it for 3 hours, filter, wash and dry it to obtain modified nano-silica, wherein the ethanol-phytic acid aqueous solution is composed of phytic acid, anhydrous ethanol and deionized water in a mass ratio of 2:7:15, the surface modification liquid is composed of tetraethylammonium bromide, 2-hydroxypyridine-3-carboxylic acid and anhydrous ethanol in a mass ratio of 0.2:3:20, and the mass ratio of the ethanol-phytic acid aqueous solution, epoxy nano-silica and the surface modification liquid is 12:4:1.

[0091] A method for preparing a flame retardant composite current collector comprises the following steps:

[0092] S1, adding modified polypropylene resin, reinforcing component, antioxidant, lubricant, coupling agent and compatibilizer into a high-speed mixer according to weight parts, mixing at a speed of 800 rpm at room temperature for 60 minutes, and mixing evenly to obtain a mixture;

[0093] S2, adding the mixed material into a twin-screw extruder, heating to 300°C, heating for 2 hours, melt extruding, and casting at a speed of 2m / min and a temperature of 200°C, and then stretching the formed material through a biaxial stretching process to form a base film layer with a thickness of 5μm, wherein the stretching temperature is 125°C, the stretching rate is 10cm / s, the heat setting temperature is 230°C, and the stretching ratio is 4:1;

[0094] S3, sputtering and depositing a copper film layer with a thickness of 5 μm on both sides of the base film layer, with a sputtering power of 550 W, a sputtering voltage of 200 V, a sputtering temperature of 180° C., a hot pressing molding temperature of 180° C., a pressure of 2 MPa, and a time of 3 min;

[0095] S4, coating a 6 μm flame retardant coating on the surface of the copper film layer by using a slot extrusion coater, drying at 60° C. for 3 h, and curing at 150° C. for 1 h to obtain a flame retardant composite current collector;

[0096] The preparation method of the flame retardant coating is as follows: disperse the polymer matrix, modified nano-silica and additives in a solvent, stir and mix, control the temperature to 230° C., stir at 400 rpm, stir for 2 hours, and obtain the flame retardant coating.

[0097] Comparative Example 1

[0098] A flame-retardant composite current collector is composed of a base film layer, a metal film layer deposited on both sides of the base film layer, and a flame-retardant layer formed by curing a flame-retardant coating coated on the surface of the metal film layer; the base film layer is made of the following raw materials in parts by weight: 100 parts of modified polypropylene resin, 10 parts of reinforcing components, 0.5 parts of antioxidants, 1 part of lubricants, 2 parts of coupling agents, and 3 parts of compatibilizers; the flame-retardant coating is made of the following raw materials in parts by weight: 10 parts of polymer matrix, 6 parts of modified nano silicon dioxide, 1 part of auxiliary agent, and 50 parts of solvent; wherein the reinforcing component is composed of nano montmorillonite and aramid fiber in a mass ratio of 5:1, the antioxidant is antioxidant 1010, the lubricant is zinc stearate, the coupling agent is γ-aminopropyl triethoxysilane, the compatibilizer is maleic anhydride grafted polypropylene, the polymer matrix is ​​polyurethane, the auxiliary agent is dimethyl silicone oil, and the solvent is N-methylpyrrolidone.

[0099] Wherein, the preparation of modified polypropylene resin comprises the following steps:

[0100] (1) placing polypropylene in a twin-screw extruder at a working temperature of 180° C. and mixing for 1.5 h to obtain intermediate 1;

[0101] (2) adding liquid crystal polymer to intermediate 1, controlling the mass ratio of intermediate 1 to liquid crystal polymer to be 10:1, operating temperature to be 230° C., mixing for 2 h, extruding granulation, and cooling to obtain intermediate 2;

[0102] (3) Disperse the intermediate 2 in toluene, heat to 80°C, stir while heating, the stirring speed is 300 rpm, and the stirring time is 10 min to obtain solution A; wherein the mass ratio of the intermediate 2 to toluene is 1:4, and dropwise add a 4-trifluoromethylbenzoyl chloride toluene solution with a mass concentration of 12% to solution A, and control the dropping time to 15 min. Meanwhile, continue stirring, control the temperature to 60°C, add pyridine, and control the mass ratio of solution A, 4-trifluoromethylbenzoyl chloride toluene solution and pyridine to 80:15:0.1, react for 1 h, filter, wash, and dry at 60°C to constant weight to obtain a modified polypropylene resin.

[0103] The preparation method of modified nano-silicon dioxide comprises the following steps:

[0104] A1. After mixing nano-silica, isopropanol, KH-570 and deionized water, ultrasonic power 50W, ultrasonic frequency 40kHz, ultrasonic for 30 minutes at room temperature, heating to 40°C, stirring for 4 hours, stirring speed 400rpm, filtering, washing and drying to obtain epoxy nano-silica, wherein the mass ratio of nano-silica, isopropanol, KH-570 and deionized water is 10:30:3:45;

[0105] A2. Add epoxy nano-silica to the ethanol-phytic acid aqueous solution, ultrasonically disperse it at 50°C for 30 minutes, with an ultrasonic power of 100 W and an ultrasonic frequency of 45 kHz, and dropwise add the surface modification liquid for 10 minutes. After the addition is completed, heat it to 100°C, stir it for 2 hours, filter, wash and dry it to obtain modified nano-silica, wherein the ethanol-phytic acid aqueous solution is composed of phytic acid, anhydrous ethanol and deionized water in a mass ratio of 1:4:10, the surface modification liquid is composed of tetraethylammonium bromide, 2-hydroxypyridine-3-carboxylic acid and anhydrous ethanol in a mass ratio of 0.1:2:15, and the mass ratio of the ethanol-phytic acid aqueous solution, epoxy nano-silica and the surface modification liquid is 10:3:0.5.

[0106] A method for preparing a flame retardant composite current collector comprises the following steps:

[0107] S1, adding modified polypropylene resin, reinforcing component, antioxidant, lubricant, coupling agent and compatibilizer into a high-speed mixer according to weight parts, and mixing at a speed of 600 rpm at room temperature for 45 minutes to obtain a mixture;

[0108] S2, adding the mixed material into a twin-screw extruder, heating to 220°C, heating for 1 hour, melt extruding, and casting at a speed of 1m / min and a temperature of 180°C, and then stretching the formed material through a biaxial stretching process to form a base film layer with a thickness of 2μm, wherein the stretching temperature is 120°C, the stretching rate is 8cm / s, the heat setting temperature is 210°C, and the stretching ratio is 4:1;

[0109] S3, sputtering and depositing a copper film layer with a thickness of 1 μm on both sides of the base film layer, with a sputtering power of 480 W, a sputtering voltage of 180 V, a sputtering temperature of 150° C., a hot pressing molding temperature of 120° C., a pressure of 1 MPa, and a time of 2 min;

[0110] S4, coating a 4 μm flame retardant coating on the surface of the copper film layer using a slot extrusion coater, drying at 50° C. for 2 h, and curing at 120° C. for 0.5 h to obtain a flame retardant composite current collector;

[0111] The preparation method of the flame retardant coating is as follows: disperse the polymer matrix, modified nano-silica and additives in a solvent, stir and mix, control the temperature to 200° C., stir at 300 rpm, stir for 1 hour, and obtain the flame retardant coating.

[0112] Comparative Example 2

[0113] A flame-retardant composite current collector is composed of a base film layer, a metal film layer deposited on both sides of the base film layer, and a flame-retardant layer formed by curing a flame-retardant coating coated on the surface of the metal film layer; the base film layer is made of the following raw materials in parts by weight: 100 parts of modified polypropylene resin, 10 parts of reinforcing components, 0.5 parts of antioxidants, 1 part of lubricants, 2 parts of coupling agents, and 3 parts of compatibilizers; the flame-retardant coating is made of the following raw materials in parts by weight: 10 parts of polymer matrix, 6 parts of modified nano silicon dioxide, 1 part of auxiliary agent, and 50 parts of solvent; wherein the reinforcing component is composed of nano montmorillonite and aramid fiber in a mass ratio of 5:1, the antioxidant is antioxidant 1010, the lubricant is zinc stearate, the coupling agent is γ-aminopropyl triethoxysilane, the compatibilizer is maleic anhydride grafted polypropylene, the polymer matrix is ​​polyurethane, the auxiliary agent is dimethyl silicone oil, and the solvent is N-methylpyrrolidone.

[0114] Wherein, the preparation of modified polypropylene resin comprises the following steps:

[0115] (1) placing polypropylene and fluorinated ethylene propylene copolymer in a mass ratio of 5:1 in a twin-screw extruder at a working temperature of 180° C. and mixing for 1.5 h to obtain an intermediate 1;

[0116] (2) Disperse the intermediate 1 in toluene, heat to 80°C, stir while heating, the stirring speed is 300 rpm, and the stirring time is 10 min to obtain solution A; wherein the mass ratio of the intermediate 1 to toluene is 1:4, and dropwise add a 4-trifluoromethylbenzoyl chloride toluene solution with a mass concentration of 12% to solution A, and control the dropping time to 15 min, while continuously stirring, and control the temperature to 60°C, add pyridine, and control the mass ratio of solution A, 4-trifluoromethylbenzoyl chloride toluene solution and pyridine to 80:15:0.1, react for 1 h, filter, wash, and dry at 60°C to constant weight to obtain a modified polypropylene resin.

[0117] The preparation method of modified nano-silicon dioxide comprises the following steps:

[0118] A1. After mixing nano-silica, isopropanol, KH-570 and deionized water, ultrasonic power 50W, ultrasonic frequency 40kHz, ultrasonic for 30 minutes at room temperature, heating to 40°C, stirring for 4 hours, stirring speed 400rpm, filtering, washing and drying to obtain epoxy nano-silica, wherein the mass ratio of nano-silica, isopropanol, KH-570 and deionized water is 10:30:3:45;

[0119] A2. Add epoxy nano-silica to the ethanol-phytic acid aqueous solution, ultrasonically disperse it at 50°C for 30 minutes, with an ultrasonic power of 100 W and an ultrasonic frequency of 45 kHz, and dropwise add the surface modification liquid for 10 minutes. After the addition is completed, heat it to 100°C, stir it for 2 hours, filter, wash and dry it to obtain modified nano-silica, wherein the ethanol-phytic acid aqueous solution is composed of phytic acid, anhydrous ethanol and deionized water in a mass ratio of 1:4:10, the surface modification liquid is composed of tetraethylammonium bromide, 2-hydroxypyridine-3-carboxylic acid and anhydrous ethanol in a mass ratio of 0.1:2:15, and the mass ratio of the ethanol-phytic acid aqueous solution, epoxy nano-silica and the surface modification liquid is 10:3:0.5.

[0120] A method for preparing a flame retardant composite current collector comprises the following steps:

[0121] S1, adding modified polypropylene resin, reinforcing component, antioxidant, lubricant, coupling agent and compatibilizer into a high-speed mixer according to weight parts, and mixing at a speed of 600 rpm at room temperature for 45 minutes to obtain a mixture;

[0122] S2, adding the mixed material into a twin-screw extruder, heating to 220°C, heating for 1 hour, melt extruding, and casting at a speed of 1m / min and a temperature of 180°C, and then stretching the formed material through a biaxial stretching process to form a base film layer with a thickness of 2μm, wherein the stretching temperature is 120°C, the stretching rate is 8cm / s, the heat setting temperature is 210°C, and the stretching ratio is 4:1;

[0123] S3, sputtering and depositing a copper film layer with a thickness of 1 μm on both sides of the base film layer, with a sputtering power of 480 W, a sputtering voltage of 180 V, a sputtering temperature of 150° C., a hot pressing molding temperature of 120° C., a pressure of 1 MPa, and a time of 2 min;

[0124] S4, coating a 4 μm flame retardant coating on the surface of the copper film layer using a slot extrusion coater, drying at 50° C. for 2 h, and curing at 120° C. for 0.5 h to obtain a flame retardant composite current collector;

[0125] The preparation method of the flame retardant coating is as follows: disperse the polymer matrix, modified nano-silica and additives in a solvent, stir and mix, control the temperature to 200° C., stir at 300 rpm, stir for 1 hour, and obtain the flame retardant coating.

[0126] Comparative Example 3

[0127] A flame-retardant composite current collector is composed of a base film layer, a metal film layer deposited on both sides of the base film layer, and a flame-retardant layer formed by curing a flame-retardant coating coated on the surface of the metal film layer; the base film layer is made of the following raw materials in parts by weight: 100 parts of modified polypropylene resin, 10 parts of reinforcing components, 0.5 parts of antioxidants, 1 part of lubricants, 2 parts of coupling agents, and 3 parts of compatibilizers; the flame-retardant coating is made of the following raw materials in parts by weight: 10 parts of polymer matrix, 6 parts of modified nano silicon dioxide, 1 part of auxiliary agent, and 50 parts of solvent; wherein the reinforcing component is composed of nano montmorillonite and aramid fiber in a mass ratio of 5:1, the antioxidant is antioxidant 1010, the lubricant is zinc stearate, the coupling agent is γ-aminopropyl triethoxysilane, the compatibilizer is maleic anhydride grafted polypropylene, the polymer matrix is ​​polyurethane, the auxiliary agent is dimethyl silicone oil, and the solvent is N-methylpyrrolidone.

[0128] Wherein, the preparation of modified polypropylene resin comprises the following steps:

[0129] (1) placing polypropylene and fluorinated ethylene propylene copolymer in a mass ratio of 5:1 in a twin-screw extruder at a working temperature of 180° C. and mixing for 1.5 h to obtain an intermediate 1;

[0130] (2) adding liquid crystal polymer to intermediate 1, controlling the mass ratio of intermediate 1 to liquid crystal polymer to be 10:1, operating temperature to be 230° C., mixing for 2 h, extruding granulation, and cooling to obtain intermediate 2;

[0131] (3) Disperse intermediate 2 in toluene, heat to 80°C, stir while heating, the stirring speed is 300 rpm, and the stirring time is 10 min to obtain solution A; wherein the mass ratio of intermediate 2 to toluene is 1:4, the temperature is controlled at 60°C, pyridine is added, and the mass ratio of solution A to pyridine is controlled to 80:0.1, react for 1 hour, filter, wash, and dry at 60°C to constant weight to obtain modified polypropylene resin.

[0132] The preparation method of modified nano-silicon dioxide comprises the following steps:

[0133] A1. After mixing nano-silica, isopropanol, KH-570 and deionized water, ultrasonic power 50W, ultrasonic frequency 40kHz, ultrasonic for 30 minutes at room temperature, heating to 40°C, stirring for 4 hours, stirring speed 400rpm, filtering, washing and drying to obtain epoxy nano-silica, wherein the mass ratio of nano-silica, isopropanol, KH-570 and deionized water is 10:30:3:45;

[0134] A2. Add epoxy nano-silica to the ethanol-phytic acid aqueous solution, ultrasonically disperse it at 50°C for 30 minutes, with an ultrasonic power of 100 W and an ultrasonic frequency of 45 kHz, and dropwise add the surface modification liquid for 10 minutes. After the addition is completed, heat it to 100°C, stir it for 2 hours, filter, wash and dry it to obtain modified nano-silica, wherein the ethanol-phytic acid aqueous solution is composed of phytic acid, anhydrous ethanol and deionized water in a mass ratio of 1:4:10, the surface modification liquid is composed of tetraethylammonium bromide, 2-hydroxypyridine-3-carboxylic acid and anhydrous ethanol in a mass ratio of 0.1:2:15, and the mass ratio of the ethanol-phytic acid aqueous solution, epoxy nano-silica and the surface modification liquid is 10:3:0.5.

[0135] A method for preparing a flame retardant composite current collector comprises the following steps:

[0136] S1, adding modified polypropylene resin, reinforcing component, antioxidant, lubricant, coupling agent and compatibilizer into a high-speed mixer according to weight parts, and mixing at a speed of 600 rpm at room temperature for 45 minutes to obtain a mixture;

[0137] S2, adding the mixed material into a twin-screw extruder, heating to 220°C, heating for 1 hour, melt extruding, and casting at a speed of 1m / min and a temperature of 180°C, and then stretching the formed material through a biaxial stretching process to form a base film layer with a thickness of 2μm, wherein the stretching temperature is 120°C, the stretching rate is 8cm / s, the heat setting temperature is 210°C, and the stretching ratio is 4:1;

[0138] S3, sputtering and depositing a copper film layer with a thickness of 1 μm on both sides of the base film layer, with a sputtering power of 480 W, a sputtering voltage of 180 V, a sputtering temperature of 150° C., a hot pressing molding temperature of 120° C., a pressure of 1 MPa, and a time of 2 min;

[0139] S4, coating a 4 μm flame retardant coating on the surface of the copper film layer using a slot extrusion coater, drying at 50° C. for 2 h, and curing at 120° C. for 0.5 h to obtain a flame retardant composite current collector;

[0140] The preparation method of the flame retardant coating is as follows: disperse the polymer matrix, modified nano-silica and additives in a solvent, stir and mix, control the temperature to 200° C., stir at 300 rpm, stir for 1 hour, and obtain the flame retardant coating.

[0141] Comparative Example 4

[0142] A flame-retardant composite current collector is composed of a base film layer, a metal film layer deposited on both sides of the base film layer, and a flame-retardant layer formed by curing a flame-retardant coating coated on the surface of the metal film layer; the base film layer is made of the following raw materials in parts by weight: 100 parts of modified polypropylene resin, 10 parts of reinforcing components, 0.5 parts of antioxidants, 1 part of lubricants, 2 parts of coupling agents, and 3 parts of compatibilizers; the flame-retardant coating is made of the following raw materials in parts by weight: 10 parts of polymer matrix, 6 parts of modified nano silicon dioxide, 1 part of auxiliary agent, and 50 parts of solvent; wherein the reinforcing component is nano montmorillonite, the antioxidant is antioxidant 1010, the lubricant is zinc stearate, the coupling agent is γ-aminopropyl triethoxysilane, the compatibilizer is maleic anhydride grafted polypropylene, the polymer matrix is ​​polyurethane, the auxiliary agent is dimethyl silicone oil, and the solvent is N-methyl pyrrolidone.

[0143] Wherein, the preparation of modified polypropylene resin comprises the following steps:

[0144] (1) placing polypropylene and fluorinated ethylene propylene copolymer in a mass ratio of 5:1 in a twin-screw extruder at a working temperature of 180° C. and mixing for 1.5 h to obtain an intermediate 1;

[0145] (2) adding liquid crystal polymer to intermediate 1, controlling the mass ratio of intermediate 1 to liquid crystal polymer to be 10:1, operating temperature to be 230° C., mixing for 2 h, extruding granulation, and cooling to obtain intermediate 2;

[0146] (3) Disperse the intermediate 2 in toluene, heat to 80°C, stir while heating, the stirring speed is 300 rpm, and the stirring time is 10 min to obtain solution A; wherein the mass ratio of the intermediate 2 to toluene is 1:4, and dropwise add a 4-trifluoromethylbenzoyl chloride toluene solution with a mass concentration of 12% to solution A, and control the dropping time to 15 min. Meanwhile, continue stirring, control the temperature to 60°C, add pyridine, and control the mass ratio of solution A, 4-trifluoromethylbenzoyl chloride toluene solution and pyridine to 80:15:0.1, react for 1 h, filter, wash, and dry at 60°C to constant weight to obtain a modified polypropylene resin.

[0147] The preparation method of modified nano-silicon dioxide comprises the following steps:

[0148] A1. After mixing nano-silica, isopropanol, KH-570 and deionized water, ultrasonic power 50W, ultrasonic frequency 40kHz, ultrasonic for 30 minutes at room temperature, heating to 40°C, stirring for 4 hours, stirring speed 400rpm, filtering, washing and drying to obtain epoxy nano-silica, wherein the mass ratio of nano-silica, isopropanol, KH-570 and deionized water is 10:30:3:45;

[0149] A2. Add epoxy nano-silica to the ethanol-phytic acid aqueous solution, ultrasonically disperse it at 50°C for 30 minutes, with an ultrasonic power of 100 W and an ultrasonic frequency of 45 kHz, and dropwise add the surface modification liquid for 10 minutes. After the addition is completed, heat it to 100°C, stir it for 2 hours, filter, wash and dry it to obtain modified nano-silica, wherein the ethanol-phytic acid aqueous solution is composed of phytic acid, anhydrous ethanol and deionized water in a mass ratio of 1:4:10, the surface modification liquid is composed of tetraethylammonium bromide, 2-hydroxypyridine-3-carboxylic acid and anhydrous ethanol in a mass ratio of 0.1:2:15, and the mass ratio of the ethanol-phytic acid aqueous solution, epoxy nano-silica and the surface modification liquid is 10:3:0.5.

[0150] A method for preparing a flame retardant composite current collector comprises the following steps:

[0151] S1, adding modified polypropylene resin, reinforcing component, antioxidant, lubricant, coupling agent and compatibilizer into a high-speed mixer according to weight parts, and mixing at a speed of 600 rpm at room temperature for 45 minutes to obtain a mixture;

[0152] S2, adding the mixed material into a twin-screw extruder, heating to 220°C, heating for 1 hour, melt extruding, and casting at a speed of 1m / min and a temperature of 180°C, and then stretching the formed material through a biaxial stretching process to form a base film layer with a thickness of 2μm, wherein the stretching temperature is 120°C, the stretching rate is 8cm / s, the heat setting temperature is 210°C, and the stretching ratio is 4:1;

[0153] S3, sputtering and depositing a copper film layer with a thickness of 1 μm on both sides of the base film layer, with a sputtering power of 480 W, a sputtering voltage of 180 V, a sputtering temperature of 150° C., a hot pressing molding temperature of 120° C., a pressure of 1 MPa, and a time of 2 min;

[0154] S4, coating a 4 μm flame retardant coating on the surface of the copper film layer using a slot extrusion coater, drying at 50° C. for 2 h, and curing at 120° C. for 0.5 h to obtain a flame retardant composite current collector;

[0155] The preparation method of the flame retardant coating is as follows: disperse the polymer matrix, modified nano-silica and additives in a solvent, stir and mix, control the temperature to 200° C., stir at 300 rpm, stir for 1 hour, and obtain the flame retardant coating.

[0156] Comparative Example 5

[0157] A flame-retardant composite current collector is composed of a base film layer, a metal film layer deposited on both sides of the base film layer, and a flame-retardant layer formed by curing a flame-retardant coating coated on the surface of the metal film layer; the base film layer is made of the following raw materials in parts by weight: 100 parts of modified polypropylene resin, 10 parts of reinforcing components, 0.5 parts of antioxidants, 1 part of lubricants, 2 parts of coupling agents, and 3 parts of compatibilizers; the flame-retardant coating is made of the following raw materials in parts by weight: 10 parts of polymer matrix, 6 parts of modified nano silicon dioxide, 1 part of auxiliary agent, and 50 parts of solvent; wherein the reinforcing component is composed of nano montmorillonite and aramid fiber in a mass ratio of 5:1, the antioxidant is antioxidant 1010, the lubricant is zinc stearate, the coupling agent is γ-aminopropyl triethoxysilane, the compatibilizer is maleic anhydride grafted polypropylene, the polymer matrix is ​​polyurethane, the auxiliary agent is dimethyl silicone oil, and the solvent is N-methylpyrrolidone.

[0158] Wherein, the preparation of modified polypropylene resin comprises the following steps:

[0159] (1) placing polypropylene and fluorinated ethylene propylene copolymer in a mass ratio of 5:1 in a twin-screw extruder at a working temperature of 180° C. and mixing for 1.5 h to obtain an intermediate 1;

[0160] (2) adding liquid crystal polymer to intermediate 1, controlling the mass ratio of intermediate 1 to liquid crystal polymer to be 10:1, operating temperature to be 230° C., mixing for 2 h, extruding granulation, and cooling to obtain intermediate 2;

[0161] (3) Disperse the intermediate 2 in toluene, heat to 80°C, stir while heating, the stirring speed is 300 rpm, and the stirring time is 10 min to obtain solution A; wherein the mass ratio of the intermediate 2 to toluene is 1:4, and dropwise add a 4-trifluoromethylbenzoyl chloride toluene solution with a mass concentration of 12% to solution A, and control the dropping time to 15 min. Meanwhile, continue stirring, control the temperature to 60°C, add pyridine, and control the mass ratio of solution A, 4-trifluoromethylbenzoyl chloride toluene solution and pyridine to 80:15:0.1, react for 1 h, filter, wash, and dry at 60°C to constant weight to obtain a modified polypropylene resin.

[0162] The preparation method of modified nano-silicon dioxide comprises the following steps:

[0163] A1. After mixing nano-silica, isopropanol, KH-570 and deionized water, ultrasonic power 50W, ultrasonic frequency 40kHz, ultrasonic for 30 minutes at room temperature, heating to 40°C, stirring for 4 hours, stirring speed 400rpm, filtering, washing and drying to obtain epoxy nano-silica, wherein the mass ratio of nano-silica, isopropanol, KH-570 and deionized water is 10:30:3:45;

[0164] A2. Add epoxy nano-silica to the ethanol aqueous solution, ultrasonically disperse it at 50°C for 30 minutes, with an ultrasonic power of 100 W and an ultrasonic frequency of 45 kHz, and drop the surface modification liquid for 10 minutes. After the addition is completed, heat it to 100°C, stir it for 2 hours, filter, wash and dry it to obtain modified nano-silica, wherein the ethanol aqueous solution is composed of anhydrous ethanol and deionized water in a mass ratio of 2:5, the surface modification liquid is composed of tetraethylammonium bromide, 2-hydroxypyridine-3-carboxylic acid and anhydrous ethanol in a mass ratio of 0.1:2:15, and the mass ratio of the ethanol aqueous solution, epoxy nano-silica and the surface modification liquid is 10:3:0.5.

[0165] A method for preparing a flame retardant composite current collector comprises the following steps:

[0166] S1, adding modified polypropylene resin, reinforcing component, antioxidant, lubricant, coupling agent and compatibilizer into a high-speed mixer according to weight parts, and mixing at a speed of 600 rpm at room temperature for 45 minutes to obtain a mixture;

[0167] S2, adding the mixed material into a twin-screw extruder, heating to 220°C, heating for 1 hour, melt extruding, and casting at a speed of 1m / min and a temperature of 180°C, and then stretching the formed material through a biaxial stretching process to form a base film layer with a thickness of 2μm, wherein the stretching temperature is 120°C, the stretching rate is 8cm / s, the heat setting temperature is 210°C, and the stretching ratio is 4:1;

[0168] S3, sputtering and depositing a copper film layer with a thickness of 1 μm on both sides of the base film layer, with a sputtering power of 480 W, a sputtering voltage of 180 V, a sputtering temperature of 150° C., a hot pressing molding temperature of 120° C., a pressure of 1 MPa, and a time of 2 min;

[0169] S4, coating a 4 μm flame retardant coating on the surface of the copper film layer using a slot extrusion coater, drying at 50° C. for 2 h, and curing at 120° C. for 0.5 h to obtain a flame retardant composite current collector;

[0170] The preparation method of the flame retardant coating is as follows: disperse the polymer matrix, modified nano-silica and additives in a solvent, stir and mix, control the temperature to 200° C., stir at 300 rpm, stir for 1 hour, and obtain the flame retardant coating.

[0171] Comparative Example 6

[0172] A flame-retardant composite current collector is composed of a base film layer, a metal film layer deposited on both sides of the base film layer, and a flame-retardant layer formed by curing a flame-retardant coating coated on the surface of the metal film layer; the base film layer is made of the following raw materials in parts by weight: 100 parts of modified polypropylene resin, 10 parts of reinforcing components, 0.5 parts of antioxidants, 1 part of lubricants, 2 parts of coupling agents, and 3 parts of compatibilizers; the flame-retardant coating is made of the following raw materials in parts by weight: 10 parts of polymer matrix, 6 parts of modified nano silicon dioxide, 1 part of auxiliary agent, and 50 parts of solvent; wherein the reinforcing component is composed of nano montmorillonite and aramid fiber in a mass ratio of 5:1, the antioxidant is antioxidant 1010, the lubricant is zinc stearate, the coupling agent is γ-aminopropyl triethoxysilane, the compatibilizer is maleic anhydride grafted polypropylene, the polymer matrix is ​​polyurethane, the auxiliary agent is dimethyl silicone oil, and the solvent is N-methylpyrrolidone.

[0173] Wherein, the preparation of modified polypropylene resin comprises the following steps:

[0174] (1) placing polypropylene and fluorinated ethylene propylene copolymer in a mass ratio of 5:1 in a twin-screw extruder at a working temperature of 180° C. and mixing for 1.5 h to obtain an intermediate 1;

[0175] (2) adding liquid crystal polymer to intermediate 1, controlling the mass ratio of intermediate 1 to liquid crystal polymer to be 10:1, operating temperature to be 230° C., mixing for 2 h, extruding granulation, and cooling to obtain intermediate 2;

[0176] (3) Disperse the intermediate 2 in toluene, heat to 80°C, stir while heating, the stirring speed is 300 rpm, and the stirring time is 10 min to obtain solution A; wherein the mass ratio of the intermediate 2 to toluene is 1:4, and dropwise add a 4-trifluoromethylbenzoyl chloride toluene solution with a mass concentration of 12% to solution A, and control the dropping time to 15 min. Meanwhile, continue stirring, control the temperature to 60°C, add pyridine, and control the mass ratio of solution A, 4-trifluoromethylbenzoyl chloride toluene solution and pyridine to 80:15:0.1, react for 1 h, filter, wash, and dry at 60°C to constant weight to obtain a modified polypropylene resin.

[0177] The preparation method of modified nano-silicon dioxide comprises the following steps:

[0178] A1. After mixing nano-silica, isopropanol, KH-570 and deionized water, ultrasonic power 50W, ultrasonic frequency 40kHz, ultrasonic for 30 minutes at room temperature, heating to 40°C, stirring for 4 hours, stirring speed 400rpm, filtering, washing and drying to obtain epoxy nano-silica, wherein the mass ratio of nano-silica, isopropanol, KH-570 and deionized water is 10:30:3:45;

[0179] A2. Add epoxy nano-silica to an ethanol-phytic acid aqueous solution, disperse by ultrasound at 50°C for 30 min, with an ultrasonic power of 100 W and an ultrasonic frequency of 45 kHz, filter, wash and dry to obtain modified nano-silica, wherein the ethanol-phytic acid aqueous solution is composed of phytic acid, anhydrous ethanol and deionized water in a mass ratio of 1:4:10, and the mass ratio of the ethanol-phytic acid aqueous solution to the epoxy nano-silica is 3:10.

[0180] A method for preparing a flame retardant composite current collector comprises the following steps:

[0181] S1, adding modified polypropylene resin, reinforcing component, antioxidant, lubricant, coupling agent and compatibilizer into a high-speed mixer according to weight parts, and mixing at a speed of 600 rpm at room temperature for 45 minutes to obtain a mixture;

[0182] S2, adding the mixed material into a twin-screw extruder, heating to 220°C, heating for 1 hour, melt extruding, and casting at a speed of 1m / min and a temperature of 180°C, and then stretching the formed material through a biaxial stretching process to form a base film layer with a thickness of 2μm, wherein the stretching temperature is 120°C, the stretching rate is 8cm / s, the heat setting temperature is 210°C, and the stretching ratio is 4:1;

[0183] S3, sputtering and depositing a copper film layer with a thickness of 1 μm on both sides of the base film layer, with a sputtering power of 480 W, a sputtering voltage of 180 V, a sputtering temperature of 150° C., a hot pressing molding temperature of 120° C., a pressure of 1 MPa, and a time of 2 min;

[0184] S4, coating a 4 μm flame retardant coating on the surface of the copper film layer using a slot extrusion coater, drying at 50° C. for 2 h, and curing at 120° C. for 0.5 h to obtain a flame retardant composite current collector;

[0185] The preparation method of the flame retardant coating is as follows: disperse the polymer matrix, modified nano-silica and additives in a solvent, stir and mix, control the temperature to 200° C., stir at 300 rpm, stir for 1 hour, and obtain the flame retardant coating.

[0186] Performance Testing

[0187] The comprehensive properties of the flame-retardant composite current collectors prepared in Examples 1-3 and Comparative Examples 1-6 of the present application are as follows:

[0188] Tensile strength and elongation at break: refer to the standard ASTMD882-12 "Standard Test Method for Tensile Properties of Films and Sheets", and use a universal tensile testing machine to test the tensile strength and elongation at break of the current collector;

[0189] Heat aging performance test: The flame retardant composite current collector is placed in hot air at 80°C and 50% relative humidity for artificial accelerated aging for 168 hours. After cooling to room temperature, the longitudinal tensile strength is measured. The heat aging performance is measured by the retention rate of the longitudinal tensile strength. The larger the value, the better the heat aging resistance.

[0190] Flame retardant performance test: The national standard GB / T 2406.2-2009 "Determination of combustion behavior of plastics by oxygen index method Part 2: Room temperature test" is used for testing. The larger the limiting oxygen index, the better the flame retardant performance;

[0191] Peel strength test: stick the tape flatly on the steel plate, fix the sample (i.e., the flame-retardant composite current collector) on the tape, stick the auxiliary tape on the surface of the sample, fix the steel plate and the auxiliary tape on the constant speed tensile machine to start the test, and record the peel strength of each sample;

[0192] The specific test results are shown in Table 1 below.

[0193] Table 1 Performance parameters of flame retardant composite current collectors in Examples 1-3 and Comparative Examples 1-6

[0194]

[0195]

[0196] As can be seen from Table 1, the flame-retardant composite current collector prepared in the present application has excellent flame retardant properties, excellent mechanical properties and heat aging resistance, high peel strength, and a strong bonding force between the metal film layer and the base film layer, which effectively improves the quality and safety of the composite current collector.

[0197] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A flame retardant composite current collector, characterized in that: The flame-retardant composite current collector consists of a base film layer, a metal film layer deposited on both sides of the base film layer, and a flame-retardant layer formed by curing a flame-retardant coating coated on the surface of the metal film layer; the base film layer is made of the following raw materials in parts by weight: 100-120 parts of modified polypropylene resin, 10-15 parts of reinforcing components, 0.5-2 parts of antioxidants, 1-3 parts of lubricants, 2-3 parts of coupling agents, and 3-5 parts of compatibilizers; the flame-retardant coating is made of the following raw materials in parts by weight: 10-12 parts of polymer matrix, 6-8 parts of modified nano-silicon dioxide, 1-2 parts of additives, and 50-60 parts of solvents.

2. The flame-retardant composite current collector according to claim 1, characterized in that: The preparation of the modified polypropylene resin comprises the following steps: (1) placing polypropylene and fluorinated ethylene propylene copolymer in a twin-screw extruder at a working temperature of 180-220° C. and mixing for 1.5-2 hours to obtain an intermediate 1; (2) adding liquid crystal polymer to intermediate 1 at a working temperature of 230-250° C., mixing for 2-3 hours, extruding granulation, and cooling to obtain intermediate 2; (3) Disperse the intermediate 2 in toluene, heat to 80-100°C, and stir while heating to obtain solution A. Add 4-trifluoromethylbenzoyl chloride toluene solution to solution A dropwise while stirring. Control the temperature at 60-80°C, add pyridine, react for 1-2h, filter, wash, and dry to obtain a modified polypropylene resin.

3. The flame retardant composite current collector according to claim 2, characterized in that: In the step (1), the mass ratio of polypropylene to fluorinated ethylene propylene copolymer is 15-20:3-6; in the step (2), the mass ratio of intermediate 1 to liquid crystal polymer is 10-12:1-2; in the step (3), the mass ratio of intermediate 2 to toluene is 2-3:8-10; in the step (3), the mass concentration of 4-trifluoromethylbenzoyl chloride toluene solution is 12-15%; in the step (3), the mass ratio of solution A, 4-trifluoromethylbenzoyl chloride toluene solution and pyridine is 80-100:15-20:0.1-1.

4. The flame-retardant composite current collector according to claim 1, characterized in that: The reinforcing component consists of nano-montmorillonite and aramid fiber in a mass ratio of 5-8:1-2.

5. The flame-retardant composite current collector according to claim 1, characterized in that: The preparation method of the flame retardant coating is as follows: a polymer matrix, modified nano silicon dioxide and an auxiliary agent are dispersed in a solvent, stirred and mixed, the temperature is controlled at 200-230° C., the stirring speed is 300-400 rpm, and the stirring is performed for 1-2 hours to obtain the flame retardant coating.

6. The flame-retardant composite current collector according to claim 1, characterized in that: The preparation method of the modified nano silicon dioxide comprises the following steps: A1. After ultrasonic mixing of nano-silica, isopropanol, KH-570 and deionized water, the mixture was heated to 40-60°C, stirred for reaction for 4-5h, filtered, washed and dried to obtain epoxy nano-silica; A2. Add epoxy nano-silica to the ethanol-phytic acid aqueous solution, disperse it by ultrasonic at 50-60°C for 30-50min, add the surface modification liquid dropwise, and after the addition is completed, heat it to 100-120°C, stir it for 2-3h, filter, wash and dry it to obtain modified nano-silica.

7. The flame-retardant composite current collector according to claim 6, characterized in that: In the step A1, the mass ratio of nano-silica, isopropanol, KH-570 and deionized water is 10-12:30-40:3-4:45-55; in the step A2, the ethanol-phytic acid aqueous solution is composed of phytic acid, anhydrous ethanol and deionized water in a mass ratio of 1-2:4-7:10-15; in the step A2, the surface modification liquid is composed of tetraethylammonium bromide, 2-hydroxypyridine-3-carboxylic acid and anhydrous ethanol in a mass ratio of 0.1-0.2:2-3:15-20, and the mass ratio of the ethanol-phytic acid aqueous solution, epoxy-based nano-silica and the surface modification liquid in the step A2 is 10-12:3-4:0.5-1.

8. A method for preparing the flame-retardant composite current collector according to any one of claims 1 to 7, characterized in that: The method comprises the following preparation steps: S1, adding modified polypropylene resin, reinforcing component, antioxidant, lubricant, coupling agent and compatibilizer into a high-speed mixer according to weight parts, and mixing uniformly to obtain a mixture; S2, adding the mixed material into a twin-screw extruder for melt extrusion, casting and forming, and then stretching the formed material through a biaxial stretching process to form a base film layer; S3, depositing metal film layers on both sides of the base film layer, and hot pressing forming; S4. Apply 4-6 μm of flame retardant coating on the surface of the metal film layer, and after drying and curing, obtain a flame retardant composite current collector.

9. The method for preparing a flame-retardant composite current collector according to claim 8, characterized in that: In the step S2, the casting speed is 1-2m / min, and the casting temperature is 180-200°C; in the step S2, the biaxial stretching process is a stretching temperature of 120-125°C, a stretching rate of 8-10cm / s, a heat setting temperature of 210-230°C, and a stretching ratio of 4:

1.

10. The method for preparing a flame-retardant composite current collector according to claim 8, characterized in that: The thickness of the base film layer in step S2 is 2-5 μm; the hot pressing molding temperature in step S3 is 120-180° C., the pressure is 1-2 MPa, and the time is 2-3 min; the curing temperature in step S4 is 120-150° C., and the curing time is 0.5-1 h.

Citation Information

Patent Citations

  • Low-temperature electrode plate, preparation method thereof and low-temperature lithium battery

    CN111816882A

  • Preparation method of composite conductive film

    CN117219354A

  • Surface treatment method of safe composite copper nano coating current collector

    CN118448639A

  • Modified polyester film for composite current collector and preparation method of modified polyester film

    CN118772472A

  • High-strength base membrane for composite current collector and preparation method of high-strength base membrane

    CN118772476A

Cited By

  • Base membrane for composite current collector based on SiO2 nano composite modification and preparation method thereof

    CN120399305A

  • High-strength sound insulation cotton and preparation method thereof

    CN120759053A

  • High-strength PP base film and preparation method thereof

    CN120842656A

  • Modified aluminum composite current collector and preparation method thereof

    CN121065680A

  • A modified aluminum composite current collector and a method for preparing the same

    CN121065680B